1977
DOI: 10.1021/bi00644a015
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I converting enzyme from human plasma

Abstract: The angiotensin I converting enzyme was purified 101 000-fold to homogeneity from human plasma by a combination of chromatographic and electrophoretic techniques. The enzyme is similar to other angiotensin I converting enzymes. It is an acidic glycoprotein consisting of a single polypeptide chain of molecular weight 140 000 with an isoelectric point of 4.6. The enzyme requires chloride ion for activity and is inhibited by ethylenediaminetetraacetic acid, angiotensin II, bradykinin, bradykinin potentiating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…In the present study, the activity of ACE was reestablished to 88% of normal activity in the presence of Nethylmaleimide, which quenches the sulphydryl group of captopril by alkylation (Lanzillo et al, 1985). The role of zinc in ACE activity was also confirmed in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, the activity of ACE was reestablished to 88% of normal activity in the presence of Nethylmaleimide, which quenches the sulphydryl group of captopril by alkylation (Lanzillo et al, 1985). The role of zinc in ACE activity was also confirmed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Affinity resins for ACE isolation have been used previously and partial purification of ACE has been achieved with several types of ligands. Multi-step protocols have been replaced progressively by simpler and less laborious chromatography procedures using an affinity gel with the potent converting enzyme inhibitor lisinopril (Lanzillo et al, 1980(Lanzillo et al, , 1985. The agarose gel affinity chromatography with lisinopril as a ligand has been used by other laboratories too (El-Dorry et al, 1982;Bull et al, 1985;Hooper and Turner, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ACE exists primarily as a membrane-bound enzyme, a soluble form is present under normal conditions in blood plasma, amniotic fluid, seminal plasma and other body fluids (reviewed in [5,7]). The enzyme in plasma seems to be catalytically identical with, and immunologically very similar to, membrane-bound somatic ACE [8], except that it lacks the hydrophobic anchoring domain [9]. While studying the mode of membrane anchorage of pig kidney ACE, we observed that the enzyme could be solubilized from the membrane in a time-and temperature-dependent manner by a post-translational proteolytic cleavage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Antiserum against human plasma ACE was prepared in rabbits as previously described (22). Monospecificity was established by Ouchterlony double diffusion and confirmed by enzyme-linked immunosorbent assay (23,24).…”
Section: Methodsmentioning
confidence: 99%